Pengaruh gaya berpikir, integritas dan usia pada perilaku kerja yang kontraproduktif - Permatasari, Mira (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2012)
This study explores the effects of thinking style, integrity and age on counterproductive work behavior (CWB). Using between subject design for 122 workers in young adulthood and 68 workers in middle adulthood, the study utilizes rational experiential inventory (REI) to determine the thinking style and self-report questionnaire to measure counterproductive work behavior and integrity. Regretion statistic found that integrity and age theirselves and interaction between them, have some effects on CWB. High-rational high-experiential thinking style have interact with integrity in affecting CWB.